Effect of laser pulse energy on laser ignition of port fuel injected hydrogen engine. (5th January 2016) - Pal, Anuj; Agarwal, Avinash Kumar
Abstract: For improving engine performance and emissions, researchers are improving combustion; and developing sustainable fuels in order to ensure global energy security. In this experimental investigation, a prototype hydrogen fuelled engine using port fuel injection was developed. A newly developed laser ignition system was installed in the test engine. Laser ignition system offers several advantages over the conventional electrical spark ignition systems such as flexibility of locating the plasma, capability to ignite leaner mixtures and significantly lower NOx emissions. In order to develop a practical laser ignition system, it is important to reduce the laser pulse energy and optimise it for best engine performance. A Q-switched Nd:YAG laser (1064 nm wavelength) with pulse duration of 6–9 ns was used for laser ignition of hydrogen–air mixture in the engine. Two laser pulse energies (16.6 mJ/pulse and 12.1 mJ/pulse) were used for the experiments and the effect of varying laser pulse energy on combustion, performance and emissions characteristics of the laser ignited hydrogen fuelled engine was evaluated experimentally. Highlights: Laser ignited hydrogen fuelled engine prototype was developed. Effect of laser pulse energy on engine combustion, performance and emissions. P, ROPR and HRR were higher for higher laser pulse energy. SOC advanced, Combustion duration shortened for higher energy pulse. Engine performance parameters improved for higher energy laser pulse.